Teacher Creativity and Student Learning Motivation on Science Achievement Results of Fifth Grade Elementary School Students - Aulia Ulin Nuha; Achmad Fathoni (International Journal of Elementary Education, 2022)
Teacher creativity is essential in learning to make the teaching and learning process fun and meaningful. The existence of creativity in the teacher will encourage students to learn. Some of the problems that developed in the field, especially the not-yet-optimal student learning outcomes, are due to teachers' low creativity and learning motivation. This study aims to analyze the effect of teacher creativity and learning motivation on the science learning achievement of fifth-grade elementary school students. This study uses a quantitative approach with an ex-post facto research design. The population is 89 students, with a total sample of 47 students using simple random sampling—data collection techniques using questionnaires and documentation. Data analysis used simple regression analysis (t-test), multiple regression analysis (F-test), and product-moment correlation. The results showed that the teacher's creativity had a positive and significant effect on the science learning achievement of fifth-grade elementary school students. Second, learning motivation has a positive and significant influence on the science learning achievement of fifth-grade students. Third, Teacher creativity and learning motivation have a positive and significant effect on the science learning outcomes of fifth-grade students of SD.